PENGARUH MODEL TEAM-ASSISTED INDIVIDUALIATION TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V - Putri Wijaya, Ayu Amirah; Margiati, KY.; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to know the effect of team-assisted individualization model to mathematics learning result on fifth grade students of Sekolah Dasar Negeri 36 Pontianak Selatan. The form of this reseacrh is quasy experimental design with nonequivalent control group design. Population of this reseacrh is 42 students and the sample of this research is 22 students of vlass VA as experiment class and 20 students of class VB as control class. To collect the data the reseacher used measuring technique which is eight of essay test. Based on research result, the mean of experiment class’s post test is 74,95, meanwhile control class’s mean is 66,3. The result of examination of hypothesis use separated varians obtained tcountisr 1,8374 and ttabel ( = 5% dan dk = 40) is 1,684 which means tcount (1,8374) > ttabel (1,684). It means there are effect team-assisted individualization model to mathematics learning result on fifth grade students of Sekolah Dasar Negeri 36 Pontianak Selatan. From the counting effect size (ES) is 0,53 and the criteria is average. Keywords : effect, team-assited individualization model, learning result.